2000
DOI: 10.1177/019262330002800601
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Lung Lesions in Female Rats Following Chronic Exposure to 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: 30 weeks, indicating that the development of these lesions required continuous exposure to TCDD. AB hyperplasia increased in an agedependent manner after DEN initiation but was unaffected by TCDD treatment. Expression of the aromatic hydrocarbon receptor (AHR) and induction of CYP1A1 was observed only in bronchiolar Clara and ciliated cells, indicating that the mechanism of induction of AB metaplasia may be mediated by the AHR. TCDD elimination half-life was monophasic in the lung, and serum and was estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
4
11
1
Order By: Relevance
“…Consistent with this concept, our previous report demonstrated a potential mechanism by which TCDD may act as a lung tumor promoter in an in vivo animal model [15]. In addition, study that used DEN as an initiator and TCDD as a promoter also showed that continuous TCDD exposure is required to promote lung tumorigenesis [1]. Thus, the tumor-promoting effect of TCDD could be the cause of its carcinogenicity, suggesting that TCDD acts as a co-carcinogen.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this concept, our previous report demonstrated a potential mechanism by which TCDD may act as a lung tumor promoter in an in vivo animal model [15]. In addition, study that used DEN as an initiator and TCDD as a promoter also showed that continuous TCDD exposure is required to promote lung tumorigenesis [1]. Thus, the tumor-promoting effect of TCDD could be the cause of its carcinogenicity, suggesting that TCDD acts as a co-carcinogen.…”
Section: Discussionsupporting
confidence: 53%
“…These compounds are formed as industrial by-products [1] and are found as persistent contaminants in the environment, food, human tissues, and human milk [2]. Human exposure to dioxins occurs mainly through contaminated food such as cow's milk, milk products, bovine adipose tissue, hen's eggs and fish [3].…”
Section: Introductionmentioning
confidence: 99%
“…The stimulus for this lesion may be damage to the preexisting epithelium due to exposure to ROS or a direct stimulation of the cells that produce certain enzymes. Clara cells are rich in catabolic enzymes, especially those of the pulmonary cytochrome P450 family (Cheville, 1994;Tritscher et al, 2000). CYP1A1 is induced by dioxins and its levels were increased in lung samples from treated animals in this study (data not shown).…”
Section: Immunohistochemical Staining For Gstpimentioning
confidence: 56%
“…The AhR is expressed in lung epithelial cells, Clara cells, and ciliated cells (31,43; our unpublished observations). Moreover, exposure of mice to TCDD induced CYP 1A1, a hallmark indicator of AhR activation, in endothelial cells of capillaries and larger vessels in the lung, type II pneumocytes, Clara cells, and bronchoepithelial cells (3,27).…”
Section: Vol 74 2006 Ahr Activation In S Pneumoniae Infection 5683mentioning
confidence: 72%